การใช้ยาไทอะโซลิดินไดโอนเพื่อชะลอการเสื่อมของเยื่อบุผนังช่องท้องจากการรักษาทดแทนไตทางช่องท้องอย่างถาวร - สิริกุล กาญจนบุษย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Objective: Peritoneal injury and neovascularization were results from continuous exposure of peritoneum to peritoneal dialysis fluid (PDF). We aimed to investigate the protective roles of pioglitazone (PGZ), PPAR- [gamma] agonist on peritoneal injury and angiogenesis in vitro and in vivo. Methods: Sprague-Dawley rats were subjected to twice-daily injections with 3.86G%PDF ± 0.1 [mu]M PGZ. After 16-wk injection, morphologies of peritoneum and vascular number were determined. In cell culture, the mesothelial cell and adipocyte injury, epithelial-to-mesenchymal transdifferentiation (EMT) and apoptosis were assessed after overnight incubation of human peritoneal mesothelial cells (HPMC) and adipocytes with 1.36G%PDF ± PGZ. Results: Vascular number, submesothelial thickness, and EMT in visceral and parietal peritoneum increased significantly while mesothelial cells disappeared in rats exposed to PDF. All the above abnormalities were markedly attenuated when co-injected with PGZ. HPMC and adipocytes cultured with PDF showed morphological changes including apoptosis. Conclusion: PGZ showed the protective roles agonist PDF-induced HPMC and adipocytes injury and peritoneal morphologic changes via PPAR-[gamma] response